2014
DOI: 10.1080/15017419.2014.941927
|View full text |Cite
|
Sign up to set email alerts
|

Aloneness and loneliness – persons with severe mental illness and experiences of being alone

Abstract: People with severe mental illness (SMI) are often described as lonely and socially incapable -an inability resulting from the mental illness. The aim of this article is to explore experiences of being alone among persons with SMI. The article is based on interviews with 19 persons diagnosed with psychosis who were interviewed between four and nine times over a period of three years. The findings show that experiences of being alone can be identified by two concepts: aloneness and loneliness. The persons in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Finally, based on the exclusion theory, Leary (1990) demonstrated that people with socialization difficulty feel excluded and lonely. Both people's inability to socialize and social rejection makes people withdraw from social life (Andersson et al, 2015). Overall, H2a summarizes the above effects:…”
Section: Figurementioning
confidence: 98%
See 3 more Smart Citations
“…Finally, based on the exclusion theory, Leary (1990) demonstrated that people with socialization difficulty feel excluded and lonely. Both people's inability to socialize and social rejection makes people withdraw from social life (Andersson et al, 2015). Overall, H2a summarizes the above effects:…”
Section: Figurementioning
confidence: 98%
“…People with financial difficulties tend to perceive lower self-esteem and have a stronger feeling of inferiority (Gilligan, 2001). Finally, a lack of money prevents people from participating in social activities and leaves them alone (Andersson et al, 2015). Moreover, monetary shortage and the need to ask friends for financial support often lead to social embarrassment and a sense of loneliness (Robila and Krishnakumar, 2005).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…This explanation is supported by the fact that in the current study, loneliness was significantly higher among the two mental illness samples, but did not significantly increase following sirens, and actually slightly decreased in the anxiety/depression group (see Figure 1 and Table 2). Elevated loneliness is common among people with mental illness during routine times (Andersson, Denhov, Bülow, & Topor, 2015). In the current study, it is not possible to know how much of it is exacerbated by the war conditions, but the unaffected or decreased loneliness under the siren condition may imply an increase in the sense of belonging.…”
Section: Discussionmentioning
confidence: 99%